Interactive Haptic System with Multimodal Tactile Sensing and Hydraulic Feedback for Realistic Human–Machine Interaction - Jingu Jeong; Mingyu Kang; Youngsup Song; Soonjae Pyo (Advanced Intelligent Systems)
With the increasing demand for immersive haptic experiences, multimodal tactile sensing and feedback have become crucial for enhancing user interaction. In this work, an interactive haptic system comprising a robotic hand and wearable tactile feedback device is introduced to facilitate tactile information exchange between humans and robots. The robotic hand, equipped with force and temperature sensors, mimics human movements through vision recognition and captures detailed tactile data. The data are then transmitted to the user through a hydraulic feedback device, providing realistic touch sensations. The dual capabilities of the hydraulic mechanism to simultaneously simulate both pressure and temperature sensations simplify the device structure and enhance reliability compared to systems that require multiple tactile actuators. The force feedback system delivers pressures ranging from 0.5 to 10.5 N across five levels while the temperature feedback mechanism provides thermal sensations ranging from 3 to 50 °C across three levels. Extensive experimental validations demonstrate the system's effectiveness in applications such as remote robotic surgery and telepresence, enabling users to perceive real‐time contact pressure and temperature during remote manipulation tasks. The proposed system, capable of delivering multimodal tactile feedback through a single actuator, represents a significant step toward more immersive and realistic haptic experiences, highlighting its broad applicability.